Test technique for turbine cooled blades of gas turbine engines. Issue 1 (May 2021) - Lepeshkin, A; Remchukov, S; Yaroslavtsev, N; Guanghua, Z; Meng, Z; Fetisov, M; Ilinskaya, O; Fedin, M; Kuleshov, A
Abstract: Test technique for turbine cooled blades of gas turbine engines is developed. The new approaches during development of inductor structures, induction heating devices, cooling systems, hydraulic force loading system and methods for their design to provide the prescribed nonuniform heating the turbine cooled blades and to carry out more effective the thermocyclic tests are presented taking into account the developed test technique. Study of effect of the clearances between inductor and blade surface and change of inductor efficiency on the thermal state of blade is presented. The test rig and improved systems of induction heating and mechanical loading are used to improve accuracy and simulate more complete the operating thermomechanical loading the full-scale cooled and uncooled blades at the thermocyclic tests. The results of rig testing the turbine cooled monocrystalline blades of gas turbine engine are received according to the developed test technique.